Perancangan Pembangkit Listrik Tenaga Surya Dengan Sudut Panel Optimal Sebagai Sumber Energi Listrik Pada Area Keramba Jaring Apung Padang Cermin - Nugroho, Bagus Agung; Setyawan, F.X Arinto; Yudamson, Afri (UNIB Press, 2024)
Indonesia's seas hold abundant natural resources and are a highly desirable location for marine fish farming, especially among fishermen. One of the most common methods used in this activity is the use of floating net cages. However, an obstacle faced by fishermen is limited access to electrical energy at the cage sites which are generally far from settlements. This research aims to design a Solar Power Plant (PLTS) in order to meet the electrical energy needs of fishermen in the floating net cage area. The focus of the research is on the design and assembly of the PLTS system with an emphasis on setting the optimal panel angle. The panel angle is calculated based on the amount of radiation received by the inclined plane surface, utilizing geographic location data obtained from NASA SSE. The results show that the proposed solar power plant design can meet the electrical energy demand in the floating net cage area. In practical implementation, the daily energy requirement of 481 Wh for lighting and automatic feeding devices can be met by using a 100 Wp solar PV system, with a battery storage capacity of 46 Ah. Furthermore, the determination of the optimal tilt angle, based on radiation and geographical factors at the location of floating net cages, is about 6 degrees, with a radiation value of 57.38848 kWh per year at the location of Padang Cermin, Durian District.